Impact of femoral varus on complications and outcome associated with corrective surgery for medial patellar luxation - Perry, Karen L.; Adams, Robert J.; Andrews, Shane J.; Tewson, Charlie; Bruce, Mieghan (Veterinary and Comparative Orthopaedics and Traumatology, 2017)
Objectives: To evaluate the association of femoral varus with postoperative complications and outcome following standard corrective surgery for medial patellar luxation (MPL) without distal femoral osteotomy (DFO) in dogs.Methods: In a retrospective study spanning a 12 year period, 87 stifles with MPL that were treated by standard surgical techniques were included. Inclination angle (ICA), femoral varus angle (FVA), anatomical lateral distal femoral angle (aLDFA), and mechanical lateral distal femoral angle (mLDFA) were measured. Postoperative complications were noted and outcome evaluated. Associations between potential risk factors and both complication rate and outcome were assessed.Results: Postoperative complications occurred in 19 stifles, five of which were major. There was no evidence of an association between FVA (p = 0.41) or aLDFA (p = 0.38) and any complication. There was also no evidence of an association between FVA (p = 0.31) or aLDFA (p = 0.38) and any major complication. Dogs with a larger aLDFA had increased odds of a poorer outcome (p = 0.01) as did dogs that suffered a major complication (p = 0.0001).Clinical significance: Based on radiographic measurements, there is no evidence of an association between FVA and the incidence of postoperative complications following standard MPL correction. Traditional surgical techniques appear to be appropriate for most cases of MPL and further work is required to better define selection criteria for including DFO in the treatment of these cases.
Keywords: Femoral varus angle; medial patellar luxation; distal femoral osteotomy; complication; canine